Improved RIP Conditions for Compressed Sensing with Coherent Tight Frames - Yao Wang; Jianjun Wang (Discrete Dynamics in Nature and Society)
This paper establishes new sufficient conditions on the restricted isometry property (RIP) for compressed sensing with coherent tight frames. One of our main results shows that the RIP (adapted to D) condition δk+θk,k<1 guarantees the stable recovery of all signals that are nearly k-sparse in terms of a coherent tight frame D via the l1-analysis method, which improves the existing ones in the literature.